The vertical distribution of epiphytic orchids on Schima wallichii trees in a montane forest in West Java, Indonesia - Indra Fardhani; Takeshi Torimaru; Hiromitsu Kisanuki (Society for Indonesian Biodiversity, 2020)
Abstract. Fardhani I, Torimaru T, Kisanuki H. 2020. The vertical distribution of epiphytic orchids on Schima wallichii trees in a montane forest in West Java, Indonesia. Biodiversitas 21: 290-298. Schima wallichii Choisy. is a mostly montane species native to the island of Java; it grows on degraded land areas and is widely used for forest restoration. We studied the vertical distribution of epiphytic orchids on these trees in montane forest on Mt. Sanggara, West Java, Indonesia. To this end, 40 S. wallichii trees with diameter at breast height (DBH) > 20 cm were chosen haphazardly and their epiphytic orchids were identified The diameter and height of each host tree were measured. The position of each epiphytic orchid on each host tree was allocated to one of five zones using Johansson’s method. In total, 39 epiphytic orchid species were identified on 40 host trees at the study site. There was no significant difference in orchid abundance or species richness between crown zones. However, there were significant differences in orchid abundance and species richness between trunks and crowns. Host tree size (DBH) and the number of branches were positively correlated with orchid abundance and species richness. The numbers of orchids and other epiphytic plants were positively correlated in the mid-crown and outer-crown. S. wallichii trees are essential for the epiphytic orchid community because they produce many branches that are suitable for colonization.